Capital de giro, internacionalização e a riqueza dos acionistas - Rezende, Cláudio Francisco (2015)
This work presents two contributions to the financial literature. First it analyzes the relationship between the degree of internationalization and the shareholder wealth. Second, it analyzes the working capital management articulated with the degree of internationalization (DOI) of the firm and their implications in shareholder wealth, supporting these relations with finance theories as the Pecking Order Theory, Theory of Asymmetric Information and Agency Theory. This work was based on Faulkender & Wang (2006) and Kieschnick, Laplante & Moussawi (2013) studies. To meet the objective of this study, we inserted an independent variable that measures the degree of internationalization of the companies. We collected data from multinational and domestic Brazilian non-financial companies listed on the BM&FBOVESPA between 2006 and 2013. First, we concluded, that there is a positive and statistically significant relationship between internationalization and the shareholder wealth. Second, an additional unit of net operating working capital, given the current levels of the degree of internationalization of the companies, reduces shareholder wealth. We suggested that the company needs funding sources to internationalize and that internationalization increases the information asymmetry and the risk for the company. So the company use at first its internal resources, according to the pecking order theory, which are also used to form the company\'s working capital, which reduces the company\'s liquidity, increases profitability and shareholder wealth. But if the company increases its level of working capital without increasing their degree of internationalization, there will be excess liquidity not used by the company that reduces the profitability and shareholder wealth. For future work, we suggest testing our results in firms of developed economies following the data examined by Faulkender and Wang (2006) and Kieschnick, Laplante and Moussawi (2013)